Nighttime Magnetic Perturbation Events Observed in Arctic Canada: 2. Multiple‐Instrument Observations. Issue 9 (9th September 2019) - Engebretson, M. J.; Steinmetz, E. S.; Posch, J. L.; Pilipenko, V. A.; Moldwin, M. B.; Connors, M. G.; Boteler, D. H.; Mann, I. R.; Hartinger, M. D.; Weygand, J. M.; Lyons, L. R.; Nishimura, Y.; et al.
Abstract: The rapid changes of magnetic fields associated with nighttime magnetic perturbations with amplitudes |Δ B | of hundreds of nanoteslas and 5‐ to 10‐min periods can induce bursts of geomagnetically induced currents that can harm technological systems. This paper presents three cases of intervals of intense and complex nighttime magnetic perturbations in eastern Arctic Canada in 2015, augmented by observations from auroral imagers and high‐altitude spacecraft in the nightside magnetosphere. Each case occurred within 1 hr after substorm onsets. None occurred during the main phase of a geomagnetic storm, and only the first during the early recovery phase (of a moderate storm). The cases were similar in that two or three intervals occurred in this region over a span of 1 hr; these showed a spatial progression, in that successive intervals occurred later at more western and northern stations. During several intervals, individual peak Bx impulses occurred nearly simultaneously (within 1–2 min) at several stations, while during others the impulses occurred later at more western and northern stations, and during one interval they occurred later at southern stations. During both of the cases for which auroral images were available, a westward traveling surge and a poleward auroral expansion and/or poleward boundary intensification occurred, and during two events auroral streamers coincided in time and location with magnetic perturbations. These observations appear to be consistent with several earlier studies connecting nighttime magnetic perturbation events to localized auroral structures and to dipolarizing flux bundles and bursty bulk flows in the magnetotail. Key Points: In each case study, two or three perturbation intervals occurred within a span of less than 1 hr; later intervals appeared to the north and west Individual perturbation events typically had a horizontal radius (center to half maximum amplitude) of 275 km Events were closely associated with auroral streamers and less closely associated with substorm onsets and magnetotail dipolarizations